(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The recent COVID-19 pandemic has largely disrupted the education system worldwide, affecting more than 1.5 billion students and learners. It has impacted teaching and learning and created many challenges for both assessment systems and practices at educational institutions worldwide. Since early 2020, because of the COVID-19 pandemic, Zhejiang University-University of Edinburgh (ZJU-UoE) biomedical science institute has changed the way they deliver teaching and learning activities and used ‘hybrid teaching’. The hybrid method of teaching involves a combination of online teaching and face-to-face teaching formats and is a blend of asynchronous (i.e., using recorded videos/material) and synchronous learning. Due to the continuing threat of the COVID-19 pandemic, there are major travel restriction and disruption to education at ZJU-UoE institute. In this article, we describe both alternative and more effective approaches and strategies to monitor and assess students that have been developed at ZJU-UoE institute during the COVID-19 pandemic. These alternative and effective approaches aimed to prioritize effective digital formative assessment, provide lecturers and tutors with extensive guidance and training, develop more creative approaches to enhance effective teacher-student interactions, and provide more support to off-campus students’ learning as well as safeguard academic integrity during the COVID-19 pandemic. This study will help with facing various education and learning challenges in a time of crisis.